Microstructure, wear performance, and mechanical properties of spark plasma-sintered AlCoCrFeNi high-entropy alloy after heat treatment. (October 2022) - Faraji, A.; Farvizi, M.; Ebadzadeh, T.; Kim, H.S.
Abstract: Powder metallurgy methods such as spark plasma sintering (SPS) are conventionally used for the fabrication of high entropy alloys (HEAs). However, the phase constituents of SPS-processed HEAs can deviate from thermodynamic predictions. With the aid of heat treatment (HT), the phase composition of HEAs can be controlled. In this study, HT at various temperatures (450, 650, and 1000 °C) was conducted on the sintered AlCoCrFeNi samples. According to microstructural studies, HT at 450 and 650 °C only slightly changed the BCC and FCC phase contents, but HT at 1000 °C led to increased FCC and decreased BCC phase fractions. Among the major phases of AlCoCrFeNi, the BCC phase exhibits greater hardness and H/E (strain to failure), and the FCC phase possesses better ductility. Therefore, due to higher BCC content, the wear rate of the sample without HT (2.61 mm 3 /N.m) was lower than that of the sample heat-treated at 1000 °C (3.15 mm 3 /N.m). On the other hand, due to the higher FCC content, the sample with HT at 1000 °C showed better compressive properties (σy = 1723 MPa, σf = 2223 MPa, and ϵ = 15%). The investigation of wear mechanisms showed that abrasive, adhesive, delamination, and oxidative mechanisms occurred in the worn samples. Also, in the fracture surfaces of samples signs of ductile fracture and brittle fracture were observed. Highlights: SPS-processed AlCoCrFeNi mainly comprised of BCC + FCC phases. HT at 450 and 650 °C did not considerably change the contents of the main phases. HT at 1000 °C enhanced FCC phase content and reduced BCC phase fraction. Due to BCC phase content reduction, heat treated sample showed lower wear resistance. Due to higher FCC content, heat treated sample indicated better compressive properties.